2004
DOI: 10.1111/j.0022-2445.2004.00013.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure and Relationship Satisfaction in Families

Abstract: The present study developed a theoretical framework for understanding the social mechanisms underlying disclosure and its link with relationship satisfaction in a full family design. A study among 262 intact families, consisting of 2 children and 2 adults and involving 1,048 individuals, applied the social relations model. Results showed that disclosure was more important to satisfaction in horizontal relationships than vertical ones. Further, relationship-specific disclosure was more important to satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
111
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 38 publications
7
111
1
5
Order By: Relevance
“…trust) significantly correlated with positive disclosure outcomes. In the general self-disclosure literature it has previously been found that disclosure increases relationship satisfaction [41]. However, this research found that the quality of the relationship may moderate the effect of disclosing.…”
Section: Discussioncontrasting
confidence: 54%
“…trust) significantly correlated with positive disclosure outcomes. In the general self-disclosure literature it has previously been found that disclosure increases relationship satisfaction [41]. However, this research found that the quality of the relationship may moderate the effect of disclosing.…”
Section: Discussioncontrasting
confidence: 54%
“…This decision produced 12 observed scores (or frequencies) of everyday talk and 12 of satisfaction (6 relationships × 2 scales; cf. Branje, van Lieshout, & van Aken, 2005;Finkenauer et al, 2004). A single social relations model analysis was then conducted to partition the variance in everyday talk and satisfaction into actor, partner, and relationship effects for each latent construct, respectively (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…To date, most of the communication research on relational satisfaction has focused primarily on romantic and married couples (e.g., Caughlin, 2002;Caughlin & Huston, 2002;Caughlin, Huston, & Houts, 2000;Miller, Caughlin, & Huston, 2003), parent-child relationships (e.g., Caughlin & Afifi, 2004;Caughlin & Golish, 2002;Sillars, Koerner, & Fitzpatrick, 2005), and general family satisfaction (e.g., Caughlin, 2003). There is, however, more recent evidence documenting various associations among disclosure patterns and relational satisfaction in first-marriage families (e.g., Finkenauer, Engels, Branje, & Meeus, 2004). Using a social relations model, Finkenauer et al (2004) found that disclosure was more important to satisfaction in horizontal family relationships (e.g., spousal and sibling dyads) than in vertical ones (e.g., father-son, mother-daughter dyads).…”
Section: Everyday Talk and Relational Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations